Nitriding of AISI 304 stainless steel by PIII in DC and RF toroidal discharges - Valencia,R. (2004)
Plasma immersion ion implantation (PIII) of stainless steels with nitrogen has been successfully used for surface hardening purposes. This process has been carried out inside a toroidal discharge chamber in a DC/RF plasma. The RF plasma was created by one antenna located inside the chamber, diametrically opposite to the DC electrode. The latter is polarized with 1 kV and then the discharge is controlled by varying the gas pressure before the RF signal is applied. The main plasma parameters were established by means of double electric probes yielding electron temperature values within 0.5-1.5 eV and density values within 1.5×10(15) to 4×10(15) m-3 for the DC case while 1.5-3.0 eV and 7×10(14) to 3×10(15) m-3 were reached with RF assisted DC. We present in this work the experimental results obtained from a PIII process applied to AISI 304 stainless steel plates. The outcome shows that the Vickers hardness has been incremented according to the gas pressure within the 1×10-1 to 1×10-3 mbar range. The treated plates were analyzed by scanning electron microscopy (SEM) and the results point to an increased percentage of nitrogen, around 20%. By means of x-ray diffractometry (XRD) the gamma expanded phase and compounds such as Fe3NiN, Ni4N, FeNiN and Fe3N were determined.